Body Fat Mass and Menarcheal Age among Indonesian Girls: Narrative Review - Rizqy Anindya Faridi; Francisca A Tjakradidjaja; Auliyani Andam Suri (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: The onset of the first menstrual period, also known as menarche, indicates the maturity of female reproductive system. Many factors influence menarcheal age. The purpose of this paper was to investigate the association between body fat mass and menarcheal age based on research articles that have been published, focusing on girls in Indonesia.Methods: The articles were encountered using Google Scholar, PubMed, and the Ministry of Education and Culture's Digital Reference. The inclusion criteria were articles published between 2017 and 2022, written in Indonesian or English, original research, conducted in Indonesia.Results: Five literature that met the inclusion and exclusion criteria were found. Four studies found a relationship between body fat mass and age at menarche. One study, however, showed the opposite conclusion.Conclusion: An increase in body fat mass can be a factor in the acceleration of menarcheal age. Girls must have a healthy body composition from an early age.